Achieving high-efficiency LaFeO3/CoS2 nanocomposite electromagnetic wave absorber for X-band stealth applications - Huang, Jian (2023)
Recently, the focus of international conflicts has shifted from military to scientific and technological with the rapid development of electronic devices, which also generate electromagnetic pollution. To overcome and/or mitigate this pollution, the fabrication of lightweight and high-efficiency microwave-absorbing materials (MAMs) has been an urgent task for the scientific community. MAMs possess significant potential across domains such as information security, 5 G communication, energy harvesting, diminished radar cross-section, and advancements in military stealth technology. Two-phase LaFeO3/CoS2 nanocomposite was fabricated to be expected as promising MAMs. Four different LaFeO3/CoS2-based MAMs showed different microwave absorption performances, where low filler loading samples showed poor features and high filler loading samples showed excellent features. MAMs with 30 and 40 wt% filler loading (named LFC-30 and LFC-40) could reach excellent values for both reflection loss (RL) and effective absorption bandwidth (EAB). The RL values were –34 and –46 dB, and the EAB values were 3.1 and 4.0 GHz for LFC-30 and LFC-40, respectively. The RL and EAB values of LFC-40 could absorb ∼99.99% of incident microwave and mostly cover the whole X band with a thin thickness of 1.6 mm. The excellent microwave absorption performance of LFC-40 could also be confirmed by the free-space method. Superior dielectric and magnetic loss tangents, rich relaxation polarization processes, good impedance matching, and a high attenuation constant could be the origins of high-efficiency MAMs in LFC-40.